2018
DOI: 10.1021/acs.jpcb.7b11384
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Gd3+ and UO22+ Ions Using Polystyrene Grafted Dibenzo Crown Ether (DB18C6) with Octanol and Nitrobenzene: A Molecular Dynamics Study

Abstract: Atomistic molecular dynamics (MD) simulations are performed in order to derive thermodynamic properties important to understand the extraction of gadolinium (Gd) and uranium dioxide (UO) with dibenzo crown ether (DBCE) in nitrobenzene (NB) and octanol (OCT) solvents. The effect of polystyrene graft length, on DBCE, on the binding behavior of Gd and UO is investigated for the first time. Our simulation results demonstrate that the binding of Gd and UO onto the oxygens of crown ethers is favorable for polystyren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 54 publications
(101 reference statements)
0
24
0
Order By: Relevance
“…This particular behavior is in good agreement with the previous gas phase theoretical results reported by Boda et al, 11 where the binding distance of 0.24 nm between Gd 3+ and O C of DBCE is reported. The previous simulation studies 27,28 have shown the Gd 3+ binding distance as ∼0.24 nm for both DBCE and DCHCE, where it is considered as a precomplexed structure as Gd 3+ -DBCE and Gd 3+ -DCHCE. However, in the present work, the binding distance between O C -Gd 3+ in water is ∼0.48 nm, which is 2 times higher than that in the gas phase.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…This particular behavior is in good agreement with the previous gas phase theoretical results reported by Boda et al, 11 where the binding distance of 0.24 nm between Gd 3+ and O C of DBCE is reported. The previous simulation studies 27,28 have shown the Gd 3+ binding distance as ∼0.24 nm for both DBCE and DCHCE, where it is considered as a precomplexed structure as Gd 3+ -DBCE and Gd 3+ -DCHCE. However, in the present work, the binding distance between O C -Gd 3+ in water is ∼0.48 nm, which is 2 times higher than that in the gas phase.…”
Section: Methodsmentioning
confidence: 94%
“…The OPLS force field is used for all the molecules such as DBCE, DCHCE, PS, HNO 3 , Gd 3+ , and NO 3 for the all atom molecular dynamics simulations . The details of all the bonded and nonbonded interactions are presented in the previous work. , We have used the TIP3P water model, and the acidic medium (1 M) is maintained by considering H 3 O + and NO 3 – ions in an aqueous solution. The particle mesh Ewald (PME) is used for calculating the electrostatic interactions with a 1 nm cutoff radius with a grid spacing of 0.1 nm and an interpolation order of 4.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed information on the force-field is given in earlier works. 22,23 The atomic charges of all molecules are taken from previous work. 22,23 Tables 1 and 2 present the bonded and nonbonded interactions, respectively.…”
Section: Methodology and Simulation Detailsmentioning
confidence: 99%